FGF-2 induces a failure of cell cycle progression in cells harboring amplified K-Ras, revealing new insights into oncogene-induced senescence. (18th June 2021) - Lund, Peder J.; Lopes, Mariana; Sidoli, Simone; Coradin, Mariel; Vitorino, Francisca Nathália de Luna; da Cunha, Julia Pinheiro Chagas; Garcia, Benjamin A.
Abstract : Cells harboring oncogenic Ras were profiled with multi-omics to understand why they senesce instead of proliferate in response to growth factor signaling. Abstract : Paradoxically, oncogenes that drive cell cycle progression may also trigger pathways leading to senescence, thereby inhibiting the growth of tumorigenic cells. Knowledge of how these pathways operate, and how tumor cells may evade these pathways, is important for understanding tumorigenesis. The Y1 cell line, which harbors an amplification of the proto-oncogene Ras, rapidly senesces in response to the mitogen fibroblast growth factor-2 (FGF-2). To gain a more complete picture of how FGF-2 promotes senescence, we employed a multi-omics approach to analyze histone modifications, mRNA and protein expression, and protein phosphorylation in Y1 cells treated with FGF-2. Compared to control cells treated with serum alone, FGF-2 caused a delayed accumulation of acetylation on histone H4 and higher levels of H3K27me3. Sequencing analysis revealed decreased expression of cell cycle-related genes with concomitant loss of H3K27ac. At the same time, FGF-2 promoted the expression of p21, various cytokines, and MAPK-related genes. Nuclear envelope proteins, particularly lamin B1, displayed increased phosphorylation in response to FGF-2. Proteome analysis suggested alterations in cellular metabolism, as evident by modulated expression of enzymes involved in purine biosynthesis, tRNA aminoacylation, and the TCA cycle. We propose that Y1 cells senesce due to an inability to progress through the cell cycle, which may stem from DNA damage or TGFb signaling. Altogether, the phenotype of Y1 cells is consistent with rapidly established oncogene-induced senescence, demonstrating the synergy between growth factors and oncogenes in driving senescence and bringing additional insight into this tumor suppressor mechanism.